Examining the Post-Traumatic Stress and Burnout among Ambulance Drivers in Tamil Nadu - M. Benson Thomas; E. Roshni Vinosha; M. Henry Pearl Louis; Y. Selvamani (Indian Journal of Social Psychiatry)
Background: Ambulance drivers are key responders of Emergency Medical Services (EMS) in the golden hours for the lifesaving of the patients. Because of their nature of work, they are exposed to a variety of physical and mental health issues in their day-to-day activities. Even though their role is crucial for their lives and patients’ survival, such information is scanty in India. Objectives: This study explores two objectives: (i) To estimate the prevalence of posttraumatic stress disorder (PTSD) and burnout among ambulance drivers in Tamil Nadu and (ii) to determine the factors affecting these mental disorders. Methods: A cross-sectional study design was employed using predesigned survey instruments to collect data from 385 samples of ambulance drivers in Tamil Nadu. The study used the Impact of Event Scale-Revised, and Maslach Burnout Inventory-Human Services Survey for Medical Personnel (MBI) to identify the symptoms of PTSD and Burnout, respectively. Subsequently, the prevalence of PTSD and burnout was estimated using descriptive statistics and a Chi-square test with background characteristics. Multivariate logistic regression (odds ratio) was used to identify the effect of these characteristics on PTSD and Burnout. Results: A high prevalence of PTSD symptoms (31%), and burnout signs (emotional exhaution – 39% and depersonalization – 63%) were found among ambulance drivers in Tamil Nadu which corroborates with that of other Asian countries. Experience of violence while performing duty, length of sleeping hours, involvement in first aid after lifesaving training, contractual job status, etc., were identified as associated factors for high PTSD, whereas experience of violence while performing duty and working hours per week were found to be associated with high burnout. Conclusion: The high prevalence of PTSD and burnout symptoms among ambulance drivers calls for an immediate need for health intervention in Tamil Nadu. It may include treatment and training for maintaining good health and work–life balance, apart from giving professional lifesaving training for ambulance service.